2008
DOI: 10.1590/s0004-282x2008000300020
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of markers Ki-67, neun, synaptophysin, p53 and HER2 in medulloblastoma and its correlation with clinicopathological parameters

Abstract: -Medulloblastoma (MB) is the most common malignant brain tumor in childhood. The alterations found include: presence of oncoproteins p53 and HER2, elevated mitotic index, and presence of neuronal differentiation. The aim of this study was to determine the immunohistochemical expression of markers Ki-67, NeuN, synaptophysin, HER2 and p53 in 40 MB samples and their correlation with clinicopathologic parameters and survival. In 29 patients (72.5%), ≥20% of cells were positive for Ki-67. Males showed greater ki-67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 24 publications
7
27
2
Order By: Relevance
“…Previous studies have demonstrated variable immunohistochemical expression of HER-2 in MBs ranging from 40 to 70% of the cases, which is compatible with our observations [4,9,10]. Although HER-2 expression in MBs was correlated with progressive disease and poor prognosis in some studies [4,10], other investigators have not proved any statistically significant association of HER-2 expression with survival [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have demonstrated variable immunohistochemical expression of HER-2 in MBs ranging from 40 to 70% of the cases, which is compatible with our observations [4,9,10]. Although HER-2 expression in MBs was correlated with progressive disease and poor prognosis in some studies [4,10], other investigators have not proved any statistically significant association of HER-2 expression with survival [9].…”
Section: Discussionsupporting
confidence: 91%
“…Although HER-2 expression in MBs was correlated with progressive disease and poor prognosis in some studies [4,10], other investigators have not proved any statistically significant association of HER-2 expression with survival [9]. In our study, we found no correlation between HER-2 expression and prognosis; nevertheless, the number of patients was small.…”
Section: Discussioncontrasting
confidence: 88%
“…This seems to be in agreement with literature since TRKC is a biomarker of apoptosis of good prognosis, and Ki67 is biomarker of cellular proliferation and poor prognosis, when presenting high levels (9,10) . We also observed a trend (p = 0.071) to a directly proportional correlation between TRKC and EGFR, so that when the first is increasing the latter increases also, which seems to be an antagonistic effect, since TRKC stimulate the apoptosis and EGFR promotes cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed a statistical trend toward Ki67 is inversely correlated with age (p = 0.088), i.e., the higher the age, the lower proliferative rate. This also seems to be in agreement with the literature, since children over 3 years of age are considered at low risk, and, consequently would have lower proliferative rates and better prognosis (Table 3) (10) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation